2016
DOI: 10.1002/jhm.2598
|View full text |Cite
|
Sign up to set email alerts
|

External validation of risk stratification strategy in the use of renal ultrasonography in the evaluation of acute kidney injury

Abstract: BACKGROUND Per the American College of Radiology Appropriateness Criteria, renal ultrasound is the most appropriate imaging examination to evaluate patients with acute kidney injury. However, recent studies suggest that renal ultrasound may be more selectively performed, which could lead to reductions in the use of medical imaging. OBJECTIVE Evaluate a published risk stratification prediction model (the Licurse model) for using renal ultrasound in hospitalized patients with acute kidney injury. DESIGN Prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Our analysis extends previous work by evaluating the role of nephrology consultation. 13 We found that risk stratification outperforms consultant recommendation, predicting 86% compared to 56% of hydronephrosis episodes. Previous analyses have found that appropriateness of certain diagnostic testing in AKI may increase when recommended by nephrology consultation rather than the primary team, however our findings did not support this for RUS.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our analysis extends previous work by evaluating the role of nephrology consultation. 13 We found that risk stratification outperforms consultant recommendation, predicting 86% compared to 56% of hydronephrosis episodes. Previous analyses have found that appropriateness of certain diagnostic testing in AKI may increase when recommended by nephrology consultation rather than the primary team, however our findings did not support this for RUS.…”
Section: Discussionmentioning
confidence: 74%
“…We found that using a risk stratification framework to guide RUS ordering for hospitalized patients with AKI predicted 86% of episodes of hydronephrosis. 9,13 The majority (60%) of RUS were ordered on medium-or low-risk patients, while only 3% of these patients were found to have hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that a risk strati cation framework predicted 86% ofepisodes of hydronephrosis in hospitalized patients with AKI whohad obtained a RUS. 11,12 The majority (60%) of RUS wereordered on medium-or low-risk patients, while only 3% of thesepatients were found to have hydronephrosis. Previous analyses havefound that appropriateness of certain diagnostic testing in AKI mayincrease when recommended by nephrology consultation, and ouranalysis extends previous validations by evaluating the role ofnephrology consultation in RUS ordering.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9][10] A risk strati cation framework to identify patients who arehigh-risk for having hydronephrosis has been previously describedand validated, but is currently underutilized. 11,12 Several factors may account for this: lack of knowledge of theframework, lack of work ow integration, and lack of assessment ofcosts of unnecessary imaging. Recommendations from nephrologistsalso inform RUS ordering for hospitalized patients with AKI,however the relationship between the risk strati cation frameworkand nephrologist recommendations is unclear.…”
Section: Introductionmentioning
confidence: 99%